Virulent Brucella nosferati infecting Desmodus rotundus has emerging potential due to the broad foraging range of its bat host for humans and wild and domestic animals - Hernández Mora, Gabriela (2023)
Desmodus rotundus, vampire bats, transmit dangerous infections, and brucellosis is a hazardous zoonotic disease, two adversities that coexist in the subtropical and tropical areas of the American continent. Here, we report a 47.89% Brucella infection prevalence in a colony of vampire bats inhabiting the tropical rainforest of Costa Rica. The bacterium induced placentitis and fetal death in bats. Wide-range phenotypic and genotypic characterization placed the Brucella organisms as a new pathogenic species named Brucella nosferati sp. nov., isolated from bat tissues, including the salivary glands, suggesting feeding behavior might favor transmission to their prey. Overall analyses placed B. nosferati as the etiological agent of a reported canine brucellosis case, demonstrating its potential for infecting other hosts. To assess the putative prey hosts, we analyzed the intestinal contents of 14 infected and 23 non-infected bats by proteomics. A total of 54,508 peptides sorted into 7,203 unique peptides corresponding to 1,521 proteins were identified. Twenty-three wildlife and domestic taxa, including humans, were foraged by B. nosferati-infected D. rotundus, suggesting contact of this bacterium with a broad range of hosts. Our approach is appropriate for detecting, in a single study, the prey preferences of vampire bats in a diverse area, demonstrating its suitability for control strategies where vampire bats thrive.